Pengaruh Rasio Keuangan dan Makroekonomi terhadap Financial Distress Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di BEI Periode 2015-2019 - Vynda Myllariza (Jurnal Ilmu Manajemen, 2021)
Financial distress is a condition that occurs in a company that is characterized by financial difficulties, and if it occurs continuously, it will cause bankruptcy, so analysis is needed to determine the factors that influence these conditions. This study aimed to determine the factors that affect the company's financial distress in the consumer goods industry sector. Predictors used as independent variables are financial ratios which include return on assets, return on equity, current ratio, debt to assets ratio, debt to equity ratio, and macroeconomics (inflation and exchange rates) to predict financial distress in companies. The type of research used is causal associative. In taking the research sample using purposive sampling technique and obtaining 26 companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2015-2019 period. Data analysis techniques in the form of logistic regression with SPSS. The results of this study indicate that the financial ratio variables used do not affect financial distress. In addition, macroeconomic variables, which include inflation and exchange rates, also have no significant effect on financial distress.